2017
DOI: 10.5301/jeppd.5000283
|View full text |Cite
|
Sign up to set email alerts
|

Trigger Point Injections for Pelvic Floor Myofascial Spasm Refractive to Primary Therapy

Abstract: defined by short, tight pelvic floor muscles with hypersensitive trigger points. It commonly presents with symptoms of overactive bladder, dyspareunia, or constipation, as well as aching, burning, clenching, or feelings of heaviness (1). Local trigger point pain may refer to distant areas or cause development of additional trigger points in surrounding muscle groups. Digital reproduction by a transvaginal or transrectal exam may elicit a local twitch response (3). The exact incidence of pelvic floor myofascial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Pelvic oor physical therapy has been reported to improve pelvic pain symptoms in 59-80% of patients with MFPP [3] [13]. Fouad et al [4] and Bartley et al [14] also demonstrated a 65% and 77% improvement in MFFP respectively for patients who received transvaginal trigger point injections. In another study that randomized 29 women to either transvaginal trigger point injections with steroid/bupivacaine or PFPT, both groups reported signi cant reduction in pain [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic oor physical therapy has been reported to improve pelvic pain symptoms in 59-80% of patients with MFPP [3] [13]. Fouad et al [4] and Bartley et al [14] also demonstrated a 65% and 77% improvement in MFFP respectively for patients who received transvaginal trigger point injections. In another study that randomized 29 women to either transvaginal trigger point injections with steroid/bupivacaine or PFPT, both groups reported signi cant reduction in pain [12].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment modalities for myofascial pelvic pain aim to relax the pelvic oor and surrounding musculature. There are various conservative and invasive approaches in management of myofascial pelvic pain, including pelvic oor physical therapy, trigger point injections (with local anesthetics and steroids), and botulinum toxin injections [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…[137][138][139] A retrospective study of 68 female participants from October 2007 to March 2015, who experienced TPIs for myofascial pelvic floor spasm, is operational in relieving pain for patients that are refractory to primary therapy. 140 The minimally invasive therapy (MIT) may be accepted, but a large, multicenter, randomized-controlled trial using a new description and upshot parameters is requisite. Likewise, transurethral needle ablation (TUNA) had also been recommended as an MIT, but a small sham-controlled study did not propose effectiveness.…”
Section: Alternative Medicinesmentioning
confidence: 99%
“…Myofascial pain syndrome arises from myofascial trigger points -exquisitely tender spots in taut bands of muscle. Myofascial pain and trigger points in the muscles of the pelvic floor is associated with dyspareunia [118,119]; in one study dyspareunia was the presenting symptom among 47% of women receiving medical treatment of pelvic floor trigger points [120], and in another 86% endorsed deep dyspareunia [121]. Whereas superficial pain has been associated with dysfunction of the outer third of the vaginal musculature, deep dyspareunia has been attributed to trigger points on the posterior levator ani or obturator internus muscles [122], perhaps because these muscles are likely to be impacted with deeper penetration.…”
Section: Myofascial Pain Syndromementioning
confidence: 99%
“…Treatment for myofascial pelvic pain includes pelvic floor physiotherapy or injection of local anesthetics and/or Botox , both of which can significantly reduce dyspareunia [120,121]. On the other hand, in a placebo controlled randomized trial, reduction in sexual pain did not differ between women treated with Botox versus saline injection [123] and a pilot randomized trial of physiotherapy versus injection with local anaesthetic and steroid showed that physiotherapy may be more efficacious in addressing deep dyspareunia [121].…”
Section: Myofascial Pain Syndromementioning
confidence: 99%